الب ا رمج التطوعية التمفزيونية ودورها في تعزيز قيم التعاون الاجتماعي لدى الطالب الجامعي د ا رسة ميدانية عمى عينة من طمبة قسم عمم الإجتماع و الديموغ ا رفيا بجامعة عمار ثميجي بالأغواط - محمد صميعة; رضية منال عباسي; عمي بوخمخال (My University, 2022)
This study aimed to identify the “voluntary television programs and their role in enhancing the values of social cooperation among university students.” To achieve this purpose, we used the descriptive approach and designed a questionnaire distributed to 128 students in the Department of Sociology at Ammar Tleji University in Laghouat. Enough programs and presenting live and modern examples of a group of youth who have succeeded and excelled in voluntary work, thus motivating young people to engage in volunteer work and enhance the values of social cooperation among them. The results showed that the voluntary content and persuasive methods of these television programs helped young people to volunteer and engage in these works, especially the presence of crises that negatively affected the environment, as bodies, groups and individuals raced to try to mitigate their impact and impact on society, and thus the youth became motivated to help and cooperate in the contribution of work. Volunteer. The study concluded with a set of recommendations, the most important of which are: activating awareness of the importance and sanctity of volunteering and its positive returns for each of the volunteers and their community through the media, especially television, and activating the media role of the culture of volunteer work and its importance in promoting the values of social cooperation among university youth.